1995
DOI: 10.1002/1097-0142(19951101)76:9<1634::aid-cncr2820760921>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

The increasing incidence of malignant gliomas and primary central nervous system lymphoma in the elderly

Abstract: Background. Studies indicate that the incidence of primary malignant brain tumors in the elderly is increasing, but this may reflect increased case ascertainment due to the introduction of computed tomography (CT) scanning. In addition, tumor histology was not available in these studies. This study was conducted to determine whether the incidence of primary malignant brain tumors in the elderly in Florida is increasing and to verify the histology of these increases. Methods. Using the number of primary maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 31 publications
2
39
1
2
Order By: Relevance
“…2 Another study showed that, although it remained relatively stable in the younger segment of the population, the incidence of GBM increased by Ͼ 20% in patients ages 70 -74 years between 1980 and 1990. 1 Even more dramatic increases (from 30% to 254%) were observed in patients age Ն 75 years. Improved diagnostic procedures may be responsible in part for the increased incidence of GBM, but they do not account for all of the changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Another study showed that, although it remained relatively stable in the younger segment of the population, the incidence of GBM increased by Ͼ 20% in patients ages 70 -74 years between 1980 and 1990. 1 Even more dramatic increases (from 30% to 254%) were observed in patients age Ն 75 years. Improved diagnostic procedures may be responsible in part for the increased incidence of GBM, but they do not account for all of the changes.…”
mentioning
confidence: 99%
“…[1][2][3] For example, some investigators have reported an increase of 5% per year in the portion of population age Ն 65 years. 2 Another study showed that, although it remained relatively stable in the younger segment of the population, the incidence of GBM increased by Ͼ 20% in patients ages 70 -74 years between 1980 and 1990.…”
mentioning
confidence: 99%
“…Most of them (70%) are astrocytic tumours, and more than 50% of these are anaplastic or Glioblastoma Multiforme. 5 Approximately, 15-20% of primary tumours in adults are meningiomas, most of them (75%) found supratentorially. 6 Out of 50 cases, 41 cases are correctly diagnosed on CT, 7 cases are incorrectly diagnosed (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…Online results had a 50% higher rate of disease recurrence compared with those with consistent results. 2,3 Similarly, among patients reclassified as being at high risk by Oncotype DX, those with conflicting Adjuvant! Online results had a recurrence rate that was 2.5 times lower compared with those with consistent results.…”
Section: Reply To Cost Effectiveness Of Gene Expression Profiling Formentioning
confidence: 99%